Differences in Beliefs About Cholesterol-Lowering Medications Among the Visegrad Group Countries: A Cross-Sectional Study - Klára Boruzs; Zita Fekete; Viktor Dombrádi; Gábor Bányai; Attila Nagy; Robert Horne; Klára Bíró (Frontiers Media S.A., 2021)
Background: New cholesterol guidelines highlight more personalized risk assessments and new cholesterol-lowering drugs for people at the highest risk for cardiovascular disease. Adherence due to fear of and lack of trust in medications prevents treatment to provide better health outcomes.Objectives: The aim of our study was to investigate the possible differences in the beliefs about the necessity and concerns regarding lipid-lowering drugs among the Visegrad Group countries.Methods: The Beliefs About Medicines Questionnaire (BMQ-Specific) was used in our research. The responses of 205 Hungarian, 200 Slovak, 235 Czech, and 200 Polish participants, all taking cholesterol-lowering medications, were compared to each other.Results: Hungarian participants' belief in the necessity of cholesterol-lowering drugs was significantly lower compared to the Slovak (P = 0.001), Czech (P = 0.037), and Polish (P < 0.001) participants. While no difference was observed between the Czech and Slovak responses (P = 0.154), both the Czech (P < 0.001) and Slovak (P = 0.006) respondents' belief regarding necessity was lower than that of the Polish. Regarding concerns, the only significant difference was observed between the Czech and the Polish respondents (P = 0.011).Conclusions: While the beliefs about benefits (necessity) are most prominent among the Polish participants, except in comparison to Czech responses, the Visegrad Group countries do not differ considerably regarding their beliefs about the fear (concerns) of the treatment.